Did paying drugs misuse treatment providers for outcomes lead to unintended consequences for hospital admissions? Difference‐in‐differences analysis of a pay‐for‐performance scheme in England. (4th May 2021) - Mason, Thomas; Whittaker, William; Jones, Andrew; Sutton, Matt
Abstract: Aims: To estimate how a scheme to pay substance misuse treatment service providers according to treatment outcomes affected hospital admissions. Design: A controlled, quasi‐experimental (difference‐in‐differences) observational study using negative binomial regression. Setting: Hospitals in all 149 organisational areas in England for the period 2009–2010 to 2015–2016. Participants: 572 545 patients admitted to hospital with a diagnosis indicating drug misuse, defined based on International Classification of Diseases 10th Revision (ICD‐10) diagnosis codes (37 964 patients in 8 intervention areas and 534 581 in 141 comparison areas). Intervention and comparators: Linkage of provider payments to recovery outcome indicators in 8 intervention organisational areas compared with all 141 comparison organisational areas in England. Outcome indicators included: abstinence from presenting substance, abstinent completion of treatment and non‐re‐presentation to treatment in the 12 months following completion. Measurements: Annual counts of hospital admissions, emergency admissions and admissions including a diagnosis indicating drugs misuse. Covariates included age, sex, ethnic origin and deprivation. Findings: For 37 245 patients in the intervention areas, annual emergency admissions were 1.073 times higher during the operation of the scheme compared with non‐intervention areas (95% CI = 1.049; 1.097). There were an estimated additional 3 352 emergency admissions in intervention areas during the scheme. These findings were robust to a range of secondary analyses. Conclusion: A programme in England from 2012 to 2014 to pay substance misuse treatment service providers according to treatment outcomes appeared to increase emergency hospital admissions.